Creep analysis of compact cross-sections cast in consecutive stages – Part 2: Algebraic methods. (1st August 2015) - Bamonte, Patrick; Pisani, Marco A.
Highlights: We model concrete compact cross-sections cast and prestressed in consecutive stages. Algebraic methods are used to determine the stress time evolution. Solution is given by means of the force method and McHenry's superposition principle. Abstract: This paper introduces an application (based on the algebraic methods) that can be used to evaluate the stress and strain time evolution of concrete compact cross-sections cast and/or prestressed in consecutive stages and exposed to long term loading. The overall cross-section may consist of a concrete, structural steel or fibre reinforced polymer component combined with the original concrete cross section at a distinct stage of the construction period or during the life of the structural element. Moreover, the cross-section can be prestressed both before and after gaining the final shape. Therefore, the application suggested in this manuscript applies to new structures cast in consecutive stages, and to specific problems involved with the rehabilitation or strengthening of concrete structures. The problem is solved by means of the force method and McHenry's superposition principle. In a following paper, a series of examples will be utilised to verify the accuracy of the application presented in this document. The results obtained by the method described in this manuscript will be compared to a refined and complex general approach introduced in a previous paper.